Goose Production Responses to Grass-Based Diets - Gyüre, Péter; Nagy, Géza; Mihók, Sándor (Acta Agraria Debreceniensis, 2004)
A feeding trial with 4 week-old goslings was conducted in 2003 using different proportions of chopped grass and grain pellets in the diet. Proportions of chopped grass and grain pellets in diets for Treatments 1, 2, 3 and 4 were 25:75; 50:50; 75:25 and 0:100, respectively. Weekly and final live weights of geese and the feather quality were measured. Treatments with higher grain contents produced higher live weights, and better feather quality.